Evaluation of Learning for Children with Special Needs in the Context of Inclusive Early Childhood Education - Saputra, Nor Ilman (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This research aims to comprehensively describe and analyze the process and follow-up of learning evaluation for Children with Special Needs within an inclusive Early Childhood Education setting. A qualitative case study approach was employed, collecting primary data through in-depth interviews with classroom teachers, the school principal, and parents, along with classroom observation and Intervention Plan document analysis. Source and method triangulation were applied to ensure the validity of the findings. The results indicate that the Children with Special Needs evaluation process in inclusive Early Childhood Education is structured, individualized, and systematic. This includes thorough planning with specific goal identification, empathetic implementation utilizing diverse assessment methods (observation, tailored tests, performance assessments), and meticulous recording to measure progress. The follow-up aspect is highly responsive, with evaluation outcomes immediately informing the design of additional programs, specific interventions, and adjustments to the curriculum and teaching methods. Key findings highlight the critical importance of active collaboration between the school and parents, supported by the principal’s managerial support in resource provision and staff coordination. In conclusion, this evaluation practice demonstrates a comprehensive, integrated, and responsive model focused on the continuous development of the children’s potential.